ANALISA KELAYAKAN APLIKASI SMART ATTENDANCE COST AND PAYMENT MENGGUNAKAN METODE USABILITY TESTING - Andita Lutfiatur Rahmadani; Yesica Novrita Devi; Danis Maulana (Proceeding Maritime Business Management Conference, 2022)
In the company, attendance has an important role in measuring the company's payroll. CV Bee Digital Prestasi Nusantara still manages attendance and payroll data using Ms. Excel where the salary calculation is done with a formula function and the resulting data is still a separate file between attendance and payroll data. This of course raises problems such as the vulnerability of financial employees to errors due to the processing of attendance and payroll data that has not been properly integrated, data that is not stored properly because it has not used a database system in its management, employee payroll reports that must be checked repeatedly according to attendance and results employee performance so that it takes a long time due to considerations of absenteeism, office work, and other interests that must be re-verified by (Human Resource Development) HRD and finance. This website-based application prototype is designed using the SDLC. As for testing, usability testing will be used in order to measure the feasibility of the system optimally. The results of testing using Usability Testing are very feasible with a total value of 86% for Ease of use, 88% for Ease of Learning, 89% for Satisfaction, and 88% for Usefulness